Estimating Market Power in Indian Telecom Industry (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Indian Telecom industry has undergone revolutionary transition from natural monopoly to competitive world since the evolution of National Telecom Policy 1994. Present study analyze and document the evolution of Market Power of Indian Telecom Industry for the period spanning 2006 to 2020, using two indicators –Markups based on De Loecker and Warzynski(2012) method and also more broadly by looking at the measure of Profitability of an individual firm and their implications on factors’ share. Result show that the aggregate markup in Telecom industry fell down from 1.21 in 2005 to 1.14 in 2019 but thereafter climbed to 1.18 in 2020. Findings of our study are robust and systematically warrant that the aggregate impact of entry of Reliance Jio(2016)put a more deterrent impact on the monopoly power(profit) as compare to the markupsof the telecom service provider . Except Jio, all the telecom players are running in loss (since 2017). So it’s a great challenge for the sustainability of the telecom service providers. Thus, it perceives a urgent need on the part of the regulatory authority to decide the ceiling on floor price or tariff taking into consideration minimum profit level (Total Revenue minus Total cost) and not on the basis of their markups (Total revenue minus Total Variable cost) in order to bring them back on track and to create the competitive environment in the telecom industry.